Improvement of the gear tooth milling process: a case study in a small company - Feriotti, Marco Aurélio; Lima Neto , Eduardo Florêncio; Formigoni, Alexandre; Martino Neto , José (Brazilian Journal of Production Engineering, 2023)
The increase in competitiveness and the pursuit of efficiency lead companies to optimize their production processes, including machining, which is widely used in the industry. This study focused on improving the gear milling process in a small company with the aim of increasing productivity. To achieve this goal, specific objectives were established, such as mapping the current process time, evaluating the tool’s lifespan, conducting practical tests with a new tool proposal, and analyzing the results. The study was based on a literature review on machining process improvements and cutting tools, and a case study using machining strategies, time mapping, and tool lifespan before and after implementing improvement measures. The test results demonstrated the effectiveness of the actions taken, such as increased production capacity and company efficiency, highlighting the proper selection of cutting tools and finding parameters as an important factor in ensuring the quality of the machining process. Continuing work on other machines in the company was suggested. This study demonstrated that optimizing the machining process can bring competitive improvements to companies.